Communication and the first steps towards the electronification of labour relations? - Homer, Zuzana; Madleňák, Adam (Technium Social Sciences Journal, 2023)
This academic paper deals with current changes to Slovak legislation in connection with the transposition of the European directive on transparent and predictable working conditions. Both authors primarily concentrate on two newly established rights related to communication between employees, employee representatives, and employers and the right to electronic communication in the business sphere between the subjects of social relations, including the right to feedback. We pay specific attention in particular to the expected impact on applied practice, which often corresponds to the authors' legal considerations of de lege ferenda. The key paradigm of the author's interpretation consists in the analysis of success in introducing a new model of communication into the more or less traditionalist approach between the subjects of labour relations, including the impact on their rights and legitimate interests.